2016
DOI: 10.1080/23265507.2016.1155168
|View full text |Cite
|
Sign up to set email alerts
|

Happiness and depression in the traditionally bullied and cyberbullied 12-year-old

Abstract: This study investigated the overall happiness, school-related happiness, and depression of traditionally bullied and cyberbullied 12-year-old Finnish students. Among the more than 700 participants, traditional bullying (26%) was more frequent than cyberbullying (18%). Receiving insulting text messages or being the subject of offensive comments on the Internet were the most common forms of cyberbullying. Often those who were cyberbullied were also victims of traditional bullying (the polyvictimized comprised 11… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
6
0
2

Year Published

2018
2018
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 12 publications
(9 citation statements)
references
References 93 publications
1
6
0
2
Order By: Relevance
“…Among the 1,457 adolescents, 24.3% of the 12-year-olds reported having been bullied, with 19.8% at age 13. This is similar to the rate of 22.4% in the United Kingdom [19], and 26% among 12-year-old Finnish students [20]. The decrease in the rate of bullying from age 12 to 13 years is in line with an international large-scale survey including 40 countries that showed a trend of decreasing prevalence in victimization with increasing age [21].…”
Section: Plos Onesupporting
confidence: 84%
See 1 more Smart Citation
“…Among the 1,457 adolescents, 24.3% of the 12-year-olds reported having been bullied, with 19.8% at age 13. This is similar to the rate of 22.4% in the United Kingdom [19], and 26% among 12-year-old Finnish students [20]. The decrease in the rate of bullying from age 12 to 13 years is in line with an international large-scale survey including 40 countries that showed a trend of decreasing prevalence in victimization with increasing age [21].…”
Section: Plos Onesupporting
confidence: 84%
“…However, those with lower level of SAS at age 12 were at higher risk of being bullied at 13, leading to lower PWB. Victims of bullying in Finland and Spain also showed a significant decrease in level of happiness, compared to adolescents who were not bullied [20,22]. Unfortunately, those with a low level of happiness are also maladapted in school and thus become more susceptible to bullying [23].…”
Section: Plos Onementioning
confidence: 99%
“…Several previous studies have confirmed the significant relationship between cyberbullying and happiness. Uusitalo-Malmivaara and Lehto [54] found that cyberbullying victims have increased symptoms of depression and a decreased level of happiness. Meanwhile, Ali Padir, Eroglu, & Caliskan [55] found a significant negative correlation between happiness and cyberbullying victimization.…”
Section: Issn: 2252-8822 mentioning
confidence: 99%
“…The positive approach could represent a counter reaction to seeing a problem in a child, as in the case of the medical model (see Reindal, 2010). Positive pedagogy is also something that has recently been written about and studied a great deal (Seligman, 2011;Uusitalo-Malmivaara & Lehto, 2016). It could be seen as a new, modern and politically acceptable way to talk about, and to approach, behavioural challenges.…”
Section: Support For Reading and Writing Mathematics And Behaviourmentioning
confidence: 99%